Insuring against bad weather - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2008)
A weather-linked micro-insurance scheme in Malawi which enables small-scale commercial farmers to insure their crops against droughts and floods.